Particle profiling of EV‐lipoprotein mixtures by AFM nanomechanical imaging - Andrea Ridolfi; Laura Conti; Marco Brucale; Roberto Frigerio; Jacopo Cardellini; Angelo Musicò; Miriam Romano; Andrea Zendrini; Laura Polito; Greta Bergamaschi; Alessandro Gori; Costanza Montis; et al. (Journal of Extracellular Vesicles, 2023)
Abstract The widely overlapping physicochemical properties of lipoproteins (LPs) and extracellular vesicles (EVs) represents one of the main obstacles for the isolation and characterization of these pervasive biogenic lipid nanoparticles. We herein present the application of an atomic force microscopy (AFM)‐based quantitative morphometry assay to the rapid nanomechanical screening of mixed LPs and EVs samples. The method can determine the diameter and the mechanical stiffness of hundreds of individual nanometric objects within few hours. The obtained diameters are in quantitative accord with those measured via cryo‐electron microscopy (cryo‐EM); the assignment of specific nanomechanical readout to each object enables the simultaneous discrimination of co‐isolated EVs and LPs even if they have overlapping size distributions. EVs and all classes of LPs are shown to be characterised by specific combinations of diameter and stiffness, thus making it possible to estimate their relative abundance in EV/LP mixed samples in terms of stoichiometric ratio, surface area and volume. As a side finding, we show how the mechanical behaviour of specific LP classes is correlated to distinctive structural features revealed by cryo‐EM. The described approach is label‐free, single‐step and relatively quick to perform. Importantly, it can be used to analyse samples which prove very challenging to assess with several established techniques due to ensemble‐averaging, low sensibility to small particles, or both, thus providing a very useful tool for quickly assessing the purity of EV/LP isolates including plasma‐ and serum‐derived preparations.